Konduktivitas termal komposit resin epoksi dan serbuk arang tempurung kelapa - Mirmanto, M.; Sugiman, S.; Fathurrahman, F.; Ramadhani, M.D. (Universitas Mataram, 2022)
Composite materials are materials that are widely developed and their use has been widespread in various industrial and household sectors. Epoxy composites filled with coconut shell charcoal powder have been tested for their thermal conductivity properties using the one-dimensional conduction method. The tested specimens had dimensions of 50 mm x 50 mm x 5 mm made of epoxy and coconut shell powder with a percentage of charcoal weight of 0%, 10%, 20% and 30%. The specimen is inserted into a thermal conductivity measuring instrument made of solid aluminum which is insulated around it. The heater is mounted on the aluminum as a heat source, while the other end is left open to the free air in the room. The results showed that the highest average thermal conductivity was a 30% variation of 0.5003 W/m°C, then a 20% variation of 0.3738 W/m°C, a 10% variation of 0.3487 W/m°C. and the lowest at 0% variation without using coconut shell charcoal powder at 0.1364 W/m°C.